New insights into the germline genes and CDR3 repertoire of the TCRβ chain in Chiroptera - Zhou, Hao; Li, Jun; Zhou, Dewei; Wu, Yingjie; Wang, Xingliang; Zhou, Jiang; Ma, Qingqing; Yao, Xinsheng; Ma, Long (Frontiers in Immunology, 2023)
Introduction Bats are recognized as natural reservoirs for many viruses, and their unique immune system enables them to coexist with these viruses without frequently exhibiting disease symptoms. However, the current understanding of the bat adaptive immune system is limited due to the lack of a database or tool capable of processing T-cell receptor (TCR) sequences for bats. Methods We performed germline gene annotation in three bat species using homologous genes and RSSs (Recombinational Signal Sequences) scanning method. Then we used the conserved C gene to construct the TCRβ chain receptor library of the Intermediate Horseshoe Bat. Bats' TCRβ data will be analyzed using MiXCR and constructed reference library. Results Regarding the annotation results, we found that the Pale Spear-nosed Bat has 37 members in the TRBV12 family, which is more than the total number of TRBV genes in the Greater Horseshoe Bat. The average number of unique TCRβ chain receptor sequences in each Intermediate Horseshoe Bat sample reached 24,904. Discussion The distinct variations in the distribution of TRBV genes among the three types of bats could have a direct impact on the diversity of the TCR repertoire, as evidenced by the presence of conserved amino acids that indicate the T-cell recognition of antigens in bats is MHC-restricted. The bats’ TCRβ repertoire is formed through the rearrangement of the V-D-J-C genes, with D-J/V-D deletions and insertions resulting in high diversity.